HUBUNGAN FAKOEMULSIFIKASI DENGAN KEJADIAN SINDROMA MATA KERING DI RSKM PADANG EYE CENTER TAHUN 2021 - Raihana Rustam; Anita Darmayanti; Chandra Adilla; Arief Rinaldy; Fetria Faisal; Mellysari Dewilis (Yayasan Nusantara Hasana Berdikari, 2023)
Dry eye syndrome is a one of disorders of the tear film caused by decreased tear production and increased tear evaporation, resulting in uncomfortable eye symptoms such as irritation, soreness, watery, sandy, sticky, itchy, red, feel sleepy, easily tired as a result there is a decrease in visual acuity when corneal epithelial damage has occurred and even perforation. This study used primary data using a questionnaire. The sample was selected by means of probability, namely consecutive sampling. The target population was cataract sufferers at RSKM Padang Eye Center who underwent cataract surgery using the phacoemulsification technique who experienced dry eye syndrome. The type of research used is analytic observation. The number of samples obtained as many as 96 people. The results of data analysis obtained that the most age was the elderly, namely 73 people (76.0%), the most gender was female, namely 59 people (61.5%), the most work was indoor, namely 54 people (56.3%), post phacoemulsification duration was the same amount between 7 days, 30 days and 3 months, namely 32 people (33.3%). With dry eye syndrome after cataract surgery at RSKM Padang Eye Center in 2021 (p=0.004). Most age are the elderly, the most gender are female, mostly work indoor, the duration of post phacoemulsification is the same between 7 days, 30 days and 3 months, most severe post-catarrhal dry eye syndrome is severe and there is a relationship between the duration of postphacoemulsification with dry eye syndrome after cataract surgery at RSKM Padang Eye Center in 2021.